Description of Kidney Histology of Mus Musculus After Giving Nano Hebal Rhodomyrtus tomentosa (Haramounting) - Syafruddin Ilyas (Talenta Publisher, 2019)
The objective of this study was to determine the description of kidney histology of Mus musculus after giving Nano Herbal Rhodomyrtus tomentosa (Haramonting). R.tomentosa (Haramonting) is made on a nanoscale using High Energy Milling (HEM). This research use the Completely Randomized Design (CRD), which consists of six groups of CMC 0.5% and Nano- R.tomentosa (Haramonting) at dosage of (100; 141,42; 200; 282,82; 400)mg/20g body weight. The kidneys were made into preparations by using the paraffin method and Hematoxylin Erlich-Eosin staining (HE). The results of histological kidneys showed that there is a significant difference (P<0,05) between control group and treatment groups with damaged cells and increased proximal tubular narrowing in kidneys, but there was not significantly different in weight of kidneys (P>0,05).